Fungicides affect the structure and function of soil microorganisms and the physiology of four riparian tree species – evidence from a pot experiment - Jacob Schnurr; Alexander Feckler; Sabine Filker; Jochen P. Zubrod; Johanna Mayer; Klaus Schützenmeister; Hermann F. Jungkunst; Mirco Bundschuh (Ecotoxicology and Environmental Safety, 2025)
Fungicides are central for global plant production strategies. Even though, direct and indirect effects on plant health were identified, they were hardly assessed, particularly not for riparian ecosystems. Known unintended side effects of fungicides are changes in soil microbial (including soil fungal) diversity and activity, but detailed surveys are rare. Here, we assessed changes in soil bacterial and fungal community structure and their carbon processing in terms of CO2 and CH4 emission under increasing fungicide concentrations crossed with four tree species, namely field maple (Acer campestre L.), rowan (Sorbus aucuparia L.), common oak (Quercus robur L.) and horse chestnut (Aesculus hippocastanum L). RNA metabarcoding uncovered that the alpha diversity of fungal communities were more affected by increasing fungicide concentrations than bacterial communities. Tree species, besides fungicide concentration, also revealed to have an impact on fungal community structure, as reflected by carbon emissions. At the same time, fungicides directly negatively affected tree height and perimeter of all four tree species. Additionally, indirect effects on plant growth through changes in the soil microbial community are possible. Being at the fringe of terrestrial to aquatic systems, riparian zones must fulfil a gatekeeper’s functions. If their functioning is weakened, matter exchanges will be less controlled.